2006
DOI: 10.1007/s10526-005-5247-1
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Milsana®, a Formulated Plant Extract from Reynoutria sachalinensis, against Powdery Mildew of Tomato (Leveillula taurica)

Abstract: The efficacy of Milsana Ò VP 1999 and 2000 (a formulated plant extract of Reynoutria sachalinensis), known to induce resistance to powdery mildew on cucumbers, was tested against Leveillula taurica (Le´v.) Arn. on greenhouse tomato. In four out of five trials, Milsana Ò achieved a disease reduction ranging from 42.2 to 64.6%. In one trial only, its efficacy was exceptionally low (23%). Application rates and disease pressure proved to be the main factors affecting the level of control. Milsana Ò was significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
29
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(34 citation statements)
references
References 11 publications
3
29
0
2
Order By: Relevance
“…It was reported that Milsana reduced powdery mildew by 90% in greenhouse-grown cucumbers under high disease pressure (Konstantinidou-Doltsinis and Schmitt, 1998). Similar success was achieved using Milsana against powdery mildew on greenhouse tomatoes with a 42.2% to 64.6% reduction in disease severity, equivalent to wettable sulphur, but less effective than fungicides (Konstantinidou-Doltsinis et al, 2006). Laboratory tests showed that Milsana had a direct effect on conidial germination of Leveillula taurica (Lév.)…”
mentioning
confidence: 67%
See 1 more Smart Citation
“…It was reported that Milsana reduced powdery mildew by 90% in greenhouse-grown cucumbers under high disease pressure (Konstantinidou-Doltsinis and Schmitt, 1998). Similar success was achieved using Milsana against powdery mildew on greenhouse tomatoes with a 42.2% to 64.6% reduction in disease severity, equivalent to wettable sulphur, but less effective than fungicides (Konstantinidou-Doltsinis et al, 2006). Laboratory tests showed that Milsana had a direct effect on conidial germination of Leveillula taurica (Lév.)…”
mentioning
confidence: 67%
“…Regalia SC is registered in the USA and other regions for use on many crops to control a number of foliar diseases both in the greenhouse and field. Except for cucumber, the extract of R. sachalinensis has been demonstrated efficacy against powdery mildew on tomato (Konstantinidou-Doltsinis et al, 2006), apple, begonia, and wheat (Herger et al, 1988) when applied proactively. It was reported that Milsana reduced powdery mildew by 90% in greenhouse-grown cucumbers under high disease pressure (Konstantinidou-Doltsinis and Schmitt, 1998).…”
mentioning
confidence: 99%
“…Furthermore, the increasing public demand for organicallygrown produce, and the intended phasing out by the EU of the use of copper-containing formulations, has precipitated an urgent need for alternative control methods. In this regard resistance-inducing treatments and substances conditioning systemic acquired resistance (SAR) are considered an alternative (MauchMani 2002;Körösi et al 2007) and there is increased interest in developing treatment strategies based on natural plant defence products (KonstantinidouDoltsinis and Schmitt 1998;Konstantinidou-Doltsinis et al 2006;Slusarenko et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…These observations indicate that protection was due to a direct effect and that no systemic effects were present. Indeed, several plant extracts have been reported to be capable of reducing diseases in plants through direct antimicrobial effects on the causal organisms (Guleria & Kumar, 2006;Konstantinidou-Doltsinis et al, 2006). Thousands of diverse natural products are produced by plants and many of these are involved in plant defence.…”
Section: Discussionmentioning
confidence: 99%